2010
DOI: 10.2113/gssgfbull.181.6.531
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow and deep temperatures in the Southeast Basin of France: Implications for local rheological contrasts

Abstract: Triassic salt at 5-10 km depth may drive some of the recent tectonic features in southeastern France. We estimate the likely temperature range of the salt using two different approaches. The first of these, based on the extrapolation of deep temperatures obtained in oil exploration wells, predicts temperatures at a depth of 8 km to be in the range of 230-300 o C. However, this prediction could be biased by a lack of deep measurements and problems related to lateral heat transfer caused by thermal conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Radiogenic heat production can contribute significantly to surface heat flow density in sedimentary basins (Frone et al 2015;Guillou-Frottier et al 2010;Schütz et al 2012;Waples 2002). In sediments, radiogenic heat production can be high in some shales especially in those rich in organic matter, like in the black shales of the Toarcian (Jurassic) encountered in the URG (Böcker et al 2017;Böcker and Littke 2016;Waples 2002).…”
Section: Evolution Of the Heat Flow Density With Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiogenic heat production can contribute significantly to surface heat flow density in sedimentary basins (Frone et al 2015;Guillou-Frottier et al 2010;Schütz et al 2012;Waples 2002). In sediments, radiogenic heat production can be high in some shales especially in those rich in organic matter, like in the black shales of the Toarcian (Jurassic) encountered in the URG (Böcker et al 2017;Böcker and Littke 2016;Waples 2002).…”
Section: Evolution Of the Heat Flow Density With Depthmentioning
confidence: 99%
“…Rittershoffen cross-section modified after Équipe du projet GeORG (2013) the GPK-1 well crosses a fracture zone at 639 m below surface with fractures with apertures on the order of millimeters (oil was detected within these fractures). The GPK-2 well crosses a fracture zone accompanied by a natural gas anomaly at 686 m and the Soultz-sous-Forêts major fault, also associated with a gas anomaly, at 708 m. If fluid migration (such as water or hydrocarbons) through these fractures occurred, or still occurs, and if the rates of migration exceed a few millimeters per year, the circulation could have induced a local thermal perturbation where the fractures cross the sedimentary formations, generating discontinuities in the heat flow density profiles (Andrews-Speed et al 1984;Guillou-Frottier et al 2010). If these fractures reach the basement (which is the case for the Kutzenhausen major fault), the thermal effect of fluid circulation in the faults could be non-negligible (Waples 2002).…”
Section: Evolution Of the Heat Flow Density With Depthmentioning
confidence: 99%
“…Presence of evaporites or salty layers in sedimentary basins may also create heat refraction processes leading to large temperature variations (case of the south-east basin in France, Guillou-Frottier et al, 2010). Around and within faulted zones, fluid circulation may also create lateral temperature differences greater than 20 °C (Clauser and Villinger, 1990;Smith, 1995, Fleming et al, 1998;Bächler et al, 2003;Wisian and Blackwell, 2004;Yang et al, 2004;Appold et al, 2007;Harcouët-Menou et al, 2009;Magri et al, 2010;Garibaldi et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previous studies demonstrated that in the subsurface, lateral temperature variations of several tens of °C can be found within a distance of a few kilometres (Pribnow and Schellschmidt, 2000;Rühaak et al, 2009;Bonté et al, 2010;Garibaldi et al, 2010;Guillou-Frottier et al, 2010). Moreover, downward extrapolation of subsurface temperature measurements through the use of an averaged regional temperature gradient may result in significant errors and could thus induce wrong decisions in geothermal exploration strategies.…”
Section: Introductionmentioning
confidence: 99%
“…According to uncertainties, we can estimate the temperature of the reservoir to be around 50°C. Considering surface water around 10°C and a regional geothermal gradient of 4°C/100m, 10 we could estimate that thermal waters flow down to 1000 m.…”
Section: Composition Of Thermal Watermentioning
confidence: 99%